Integron-mediated multidrug resistance in extended-spectrum β-lactamase-producing Escherichia coli and Klebsiella pneumoniae isolated from fecal specimens in Egypt. Issue 2 (June 2016) - Elsherif, Rasha H.; Ismail, Dalia K.; El-Kholy, Yasmine S.; Gohar, Noha M.; Elnagdy, Sherif M.; Elkraly, Omnia A.
Abstract : Background: The increasing incidence of hospital-acquired infections due to extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae represent a major health problem because of few therapeutic alternatives. The fecal flora can represent a reservoir for ESBL genes. Integrons are genetic structures capable of capturing gene cassettes that usually encode antibiotic-resistance determinants. Objectives: To investigate the antimicrobial susceptibility of fecal isolates of ESBL-producing Escherichia coli and Klebsiella pneumoniae from hospitalized and nonhospitalized Egyptian patients and to determine the prevalence of class 1 and class 2 integrons together with the most common ESBL-producing genes (bla TEM, SHV, CTX-M, and OXA ) among the collected isolates. Materials and methods: Ninety-six fecal samples were collected: 48 samples from hospitalized patients admitted at Kasr Al-Ainy University Hospital, Cairo and 48 from outpatient clinics. Samples were inoculated on MacConkey agar and identified. All isolates were tested for their susceptibility to different antimicrobial agents using a standard disk diffusion method. The double-disk synergy test was applied for screening ESBL. All ESBL-producing isolates were confirmed by molecular testing to detect ESBL-encoding genes ( SHV, TEM, CTX-M, and OXA ). To identify the strains carrying integrons 1 and 2, the conserved regions of integron-encoded integrase gene intI1 and intI2 were amplified. Results: E. coli isolates accounted for 52.1% of the isolates collected from hospitalized patients and 60.4% of those collected from outpatient clinics. Results of the double-disk synergy test were positive in all E. coli and K. pneumoniae isolates, indicating the presence of ESBL production. Isolates of both groups showed variably high degrees of resistance to ciprofloxacin and co-trimoxazole. The most predominant ESBL gene in both groups was the bla CTX-M gene (93.8%) and the least prevalent was the bla OXA gene, which was not detected in any of the study isolates. Between the other two genes, the bla TEM gene was more common than the bla SHV gene in the two study groups. Class 1 integron was more prevalent among hospitalized patients, being detected in 64.6% of isolates from this group. Class 1 integron was linked with the bla CTX-M gene ( P =0.039). Class 2 integron was more prevalent in the nonhospitalized group (85.4%) compared with the hospitalized group (50%) ( P <0.001). Conclusion and recommendations: ESBL-producing E. coli and K. pneumoniae showed a marked degree of antibiotic resistance in both hospitalized and nonhospitalized study groups. The high prevalence of class 1 and 2 integrons among isolates of both groups has a serious impact on the spread of antibiotic resistance.